Impairment of motor skills in children with fetal alcohol spectrum disorders in remote Australia: The Lililwan Project. (16th February 2016) - Lucas, Barbara R.; Doney, Robyn; Latimer, Jane; Watkins, Rochelle E.; Tsang, Tracey W.; Hawkes, Genevieve; Fitzpatrick, James P.; Oscar, June; Carter, Maureen; Elliott, Elizabeth J.
Abstract: Introduction and Aims: We aimed to characterise motor performance in predominantly Aboriginal children living in very remote Australia, where rates of prenatal alcohol exposure (PAE) are high. Motor performance was assessed, and the relationship between motor skills, fetal alcohol spectrum disorders (FASD) and PAE was explored . Design and Methods: Motor performance was assessed using the Bruininks–Oseretsky Test of Motor Proficiency—Second Edition Complete Form, in a population‐based study of children born in 2002 or 2003 living in the Fitzroy Valley, Western Australia. Composite scores ≥2SD (2nd percentile) and ≥1SD (16th percentile) below the mean were used respectively for FASD diagnosis and referral for treatment. FASD diagnoses were assigned using modified Canadian Guidelines . Results: A total of 108 children (Aboriginal: 98.1%; male: 53%) with a mean age of 8.7 years was assessed. The cohort's mean total motor composite score (mean ± SD 47.2 ± 7.6) approached the Bruininks–Oseretsky Test of Motor Proficiency—Second Edition normative mean (50 ± 10). Motor performance was lower in children with FASD diagnosis than without (mean difference (MD) ± SD: −5.0 ± 1.8; confidence interval: −8.6 to −1.5). There was no difference between children with PAE than without (MD ± SE: −2.2 ± 1.5; confidence interval: −5.1 to 0.80). The prevalence of motor impairment (≥−2SD) was 1.9% in the entire cohort, 9.5% in children with FASD, 3.3% in children with PAE and 0.0% both in children without PAE or FASD . Discussion and Conclusions. Almost of 10% of children with FASD has significant motor impairment. Evaluation of motor function should routinely be included in assessments for FASD, to document impairment and enable targeted early intervention. [Lucas BR, Doney R, Latimer J, Watkins RE, Tsang TW, Hawkes G, Fitzpatrick JP, Oscar J, Carter M, Elliott EJ. Impairment of motor skills in children with fetal alcohol spectrum disorders in remote Australia: The Lililwan Project. Drug Alcohol Rev 2016;35:719–727]